Faktor – faktor yang mempengaruhi indeks pembangunan manusia di Provinsi Papua Tahun 2015-2019 - Mandu Chaironi; Jalu Aji Prakoso (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
This research makes use of secondary facts with panel data evaluation, consisting of time series records for 2015-2019 and go section facts for 27 towns/districts in Papua Province. The secondary statistics taken encompass the Human improvement Index (HDI), Gross regional domestic Product (GRDP), income distribution, and poverty levels. The consequences of this have a look at indicate that there's a positive have an impact on among profits distribution at the Human development Index (HDI), poverty level which has a significant poor impact at the Human improvement Index (HDI), and profits distribution which has a high quality impact on the Human development Index (IPM) in Papua Province. 2015-2019 years.